PERSEPSI NASABAH UNIVERSITAS ISLAM NEGERI SUMATERA UTARA TERHADAP LAYANAN FITUR MOBILE BANKING BSI - Askur Hamid Nst (EKSYA : Jurnal Ekonomi Syariah, 2023)
This study aims to determine customer perceptions at the State Islamic University of North Sumatra on the use of feature services in the Bank Syariah Indonesia Mobile Banking application. Previously, making transactions such as transfers, cash withdrawals, and so on, someone had to go to the nearest bank office. With very rapid technology, a bank application is formed where all transactions can be carried out or now called Mobile Banking. provide information on the features contained in BSI mobile banking and customer perceptions of BSI mobile banking users. Of course there is customer satisfaction and dissatisfaction with the services provided by BSI mobile banking but it does not reduce the sense of convenience and logic of mobile banking users.